(untitled) (The Pakistan Development Review, 1993)
Health care systems in both developing and developed countries are in a state of crisis. The burden of providing medical care for those who require it is stretching government budgets’. To reduce the pressure on the budgets, alternative measures, e.g., the introduction of a user fee, have been taken so that the responsibility of financing health care is shared by all. The use of such fees has become common practice even in developing countries like India, where socialised medicine has formed a major plank of social development. This crisis in the financing of health care systems has resulted in the publication of numerous articles and books describing the problems and suggesting the methods for their solution, as well as experimenting with novel ways to provide the finances needed for an efficient health care system. Thus, this book has been published at a very opportune time.